Report on the Observance of Standards and Codes : Corporate Governance Country Assessment - Pakistan 2018 - World Bank (World Bank, Islamabad, 2019)
This report assesses Pakistan’s corporate governance policy framework. It highlights recent improvements in corporate governance regulation, makes policy recommendations, and provides investors with a benchmark against which to measure corporate governance in Pakistan. The report focuses on the governance of large and listed companies, but includes a special section on the governance of public sector companies. The report highlights that corporate governance framework for listed companies has improved in recent years as the government has enhanced the legal and policy framework, and key institutions have grown in sophistication and maturity. Much more can be done to address corporate governance in Public Sector Companies. The findings of the Report on the Observance of Standards and Codes (ROSC) are based on the Detailed Country Assessment (DCA) of the OECD Principles of Corporate Governance, which is summarized in the tables at the end of each section. According to the World Bank methodology used to assess compliance with the 72 OECD Principles, 20 Principles were fully implemented, 33 were broadly implemented, 16 principles were partially implemented, and three were not applicable. A comparison with the 2005 Corporate Governance ROSC shows the level of improvement in the corporate governance framework; in 2005 out of a total of 32 applicable principles, only 4 were fully implemented, 17 were broadly implemented, 10 were partially implemented and 1 was reported as not implemented. The report (and this summary) is organized into five sections: The commitment of the public and private sectors to reform; Shareholder rights; Disclosure and transparency; Boards of directors and Public sector companies.